2019
DOI: 10.1002/star.201900204
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Composites of Hydroxypropyl Tapioca Starch and Zein

Abstract: Hydroxypropyl tapioca starch and zein composites are prepared and the properties of composites are investigated. Starch granules can readily aggregate in the presence of zein to form large granules more than 30 µm. The total preparation concentration of zein and starch of 45% can be critical, as inferred from the relation between the zein content and the particle size of the composite. An increase of zein content or reaction time allows the starch granules to be adhered with zein, wrapped by zein, or even be e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Because the amylose content of the system plays an important role in hardness determination, and the reduction in amylose content causes lower firmness and weakens the gel structure [ 19 , 32 ]. In addition, Liu et al [ 33 ] reported that the gel firmness is primarily influenced by leached amylose rearrangement rather than amylopectin retrogradation. In the present study, the starch content of the system was constant, but the gel hardness decreased after the MBPI addition.…”
Section: Resultsmentioning
confidence: 99%
“…Because the amylose content of the system plays an important role in hardness determination, and the reduction in amylose content causes lower firmness and weakens the gel structure [ 19 , 32 ]. In addition, Liu et al [ 33 ] reported that the gel firmness is primarily influenced by leached amylose rearrangement rather than amylopectin retrogradation. In the present study, the starch content of the system was constant, but the gel hardness decreased after the MBPI addition.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, a composite was prepared consisting of hydroxypropyl tapioca starch and zein. The results showed that an increased zein level or reaction time caused the starch granules to adhere to or be wrapped by the zein and were even embedded in the zein matrix [ 29 ]. Leroy et al observed the dispersion of large starch aggregates into a continuous zein matrix at a zein content level exceeding 50% [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Luo et al reported that microwave treatment did not alter the sizes and shapes of the granules in normal maize, waxy maize, and amylomaize V starches [ 32 ], while those of the composite increased significantly ( p < 0.05), which was consistent with the scanning electron micrographs. The encapsulation of the protein around starch granules causes agglomeration, increasing their average particle sizes [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…The foregoing topics on a polysaccharide–protein interaction also apply to the combination of starch and vegetable protein. There are several works dealing with functional properties of starch systems containing pea protein, [ 12 ] lentil protein, [ 13–15 ] soy protein, [ 2,16–19 ] corn protein (zein), [ 20 ] or potato protein. [ 11 ] It was evidenced that these protein mixtures provided distinctive functionality depending on the nature of the polymers, their concentrations, and processing conditions (for example pH).…”
Section: Introductionmentioning
confidence: 99%